Epidemiological Profile of Cancer Patients Received Radiotherapy Treatment in A Tertiary Care Teaching Hospital - Saad Jamal; Furrukh; Asma Saleem Khan; Asif Husain Osmani; Shoaib Hanif; Quratul Ain Badar; Jawaid Mallick (Pakistan Journal of Medicine and Dentistry)
Background: Cancer is the second leading cause of death around the world and is one of the most serious non-contagious diseases. Its incidence and demography form the basis of prevention and screening. However, existing data from cancer registries is limited in our part of the world. This study is powered to discuss the epidemiological profile of cancer patients for radiation treatment in a calendar year.